Treatment of Severe Refractory Hematuria due to Radiation-Induced Hemorrhagic Cystitis with Dexamethasone - José Carlos Rodrigues Nascimento; Márcio Wilker Soares Campelo; Iuri Arruda Aragão; José Fernando Bastos de Moura; Lúcio Flávio Gonzaga Silva; Reinaldo Barreto Oriá (Case Reports in Medicine)
Treatment of pelvic neoplasms with radiotherapy may develop sequelae, especially RHC. An 85-year-old male patient was admitted to a hospital emergency with gross hematuria leading to urinary retention and was diagnosed with RHC. The urinary bladder was probed, unobstructed, and maintained in continuous three-way saline irrigation. During 45 days of hospitalization, the patient underwent two cystoscopic procedures for urinary bladder flocculation, whole blood transfusions, and one platelet apheresis. None of these interventions led to clinical resolution. As the patient hematological condition was deteriorating, dexamethasone (4 mg i.v., bolus of 6/6, 12/12, and 24 h during five days) and epoetin alpha (1000 IU, 1 ml, s.c., for four weeks) were administered which led to the remission of the urinary bleeding. Dexamethasone therapy may be considered for RHC, when conventional treatments are not effective or are not possible, avoiding more aggressive interventions such as cystectomy.